Application of STAD Cooperative Model in Learning to Analyze the Systematics of Essay Texts and Literary Criticism - Wulandari, Ririn (Universitas Swadaya Gunung Jati, 2024)
This study aims to describe the results of students' work on worksheets and determine students' responses to the STAD type cooperative model in learning to analyze the systematics of essay texts and literary criticism. The subjects in this study were students of class XII MIPA 2 SMAN 4 Kota Cirebon. In this study, the method used was classroom action research method with descriptive analysis technique. The results showed the results of students' analysis in learning to analyze the systematics of essays and literary criticism obtained an average score of 92.88 from a total of 28 students with the highest score of 100 and the lowest score of 70. Meanwhile, students' responses to learning by using the STAD type cooperative model obtained good results. This can be seen from the percentage of each indicator which tends to be high in the “agree” option. Nevertheless, there are still percentages that show students' disagreement with the questions asked. For example, in the indicators of gathering information, collaboration, and finalizing the results of the analysis which has a fairly high percentage compared to other indicators.